Spatial prediction of winter wheat yield gap: agro-climatic model and machine learning approaches - Mousavi, Seyed Rohollah; Jahandideh Mahjenabadi, Vahid Alah; Khoshru, Bahman; Rezaei, Meisam (Frontiers in Plant Science, 2024)
This study aimed to identify the most influential soil and environmental factors for predicting wheat yield )WY( in a part of irrigated croplands in southwest Iran, using the FAO-Agro-Climate method, and machine learning algorithms (MALs). A total of 60 soil samples and wheat grain (1×1m) in 1200 ha of Pasargad plain were collected and analyzed in the laboratory. Attainable WY was assessed using the FAO method for the area. Pearson correlation analysis was used to select the best set of soil properties for modeling. Topographic attributes and vegetation indices were used as proxies of landscape components and cover crop to map actual WY in the study area. Two well-known MLAs, random forest (RF) and artificial neural networks (ANNs), were utilized to prepare an actual continuous WY map. The k-fold method was used to determine the uncertainty of WY prediction and quantify the quality of prediction accuracy. Results showed that soil organic carbon (SOC) and total nitrogen (TN) had a positive and significant correlation with WY. The SOC, TN, normalized different vegetation index (NDVI), and channel network base level (CHN) were recognized as the most important predictors and justifying more than 50% of actual WY.. The ANNs outperformed the RF algorithm with an R2 of 0.75, RMSE of 400 (kg ha-1), and RPD of 2.79, according to statistical indices. The uncertainty analysis showed that the maximum uncertainty of the prediction map (400 (kg ha-1)) was very low compared to the mean value (4937 (kg ha-1)) of WY map. Calculation yield gap using the FAO-Agro-Climatic model showed that the average yield gap of the region was about 50% of actual yield. The findings of this study demonstrated that integrating simulated attainable crop growth using crop model and a set of soil and environmental covariates with the ANNs algorithm can effectively predict WY gaps in large areas with acceptable and reasonable accuracy. The study emphasizes that the implementation of efficient management practices has the potential to enhance agricultural production in the study area and similar regions. These results represent a significant advancement ofsustainable agriculture and provide valuable insights for ensuring global food security.